Ruptured intracranial aneurysms: the overall effect of treatment and the influence of patient selection and data presentation on the reported outcome. Issue 12 (December 1985) - Maurice-Williams, R S; Marsh, H
Abstract : An attempt is made to assess the overall impact of current treatment of ruptured intracranial aneurysms, based on the outcome in 200 consecutive patients, unselected in that they were transferred to neurosurgical care as soon as they were referred, regardless of clinical condition. Overall mortality at 1 year was 35.5%. It is estimated that at the present time treatment improves the one-year survival of patients who reach the primary care hospital by no more than 12-15%. In assessing the apparent benefits of treatment, it is easy to overlook the effects of patient selection and the way in which data are presented. Other admission policies in line with current practice but involving greater selectivity and delay in transfer, could have reduced the one-year mortality of this series of patients to 16.1%, by excluding from neurosurgical care patients who were in a poor condition or about to deteriorate. The outcome data in this series could be presented in different ways so as to represent the surgical mortality as ranging between 13.8% and 3.3%.